Spinal Dural Arteriovenous Fistulas: Surgical Outcome Analysis of Twenty Cases (Bangladesh Journal of Neurosurgery, 2024)
Background: Spinal dural arteriovenous fistulas (SDAVFs) are rare complex spinal vascular shunts, which caninevitably lead to severe disability if remain untreated.Methods: Retrospective analysis of SDAVFs patientsina period of three years (2019 to 2021) who presented with progressive paraparesis, bladder symptoms and/or sensory disturbances. They were evaluated by MRI and localization of the fistula was done by spinal catheter angiogram. Spinal AV fistulas were simply classified as extradural and intradural.They all underwent microsurgical shunt interruption. Neurological function was evaluated by Aminoff-Logue Scale (ALS) consecutively at the day before surgery, 6 months and 1year after surgery. Results: A total of 20 patients (mean age 35 ± 10 years, 16 (80.0%) are male.The mean interval from onset to diagnosis was 6 ± 3 months. Among the anatomical location of fistulas, 1(05.0%) was in cervical, 16 (80.0%)were inthoracic, and 3 (15.0%) were in lumbar. Among the angiographic types of fistulas, 18(90.0%) were intradural and,2(10.0%) were extradural.Mean pre-treatment ALS was 5.3 and mean last examination ALS was 3.9. There was a significant improvement of the ALS between pretreatment and last examination ALS (P = 0.0009). Among 20 surgical procedures there were complications in three cases (15%): epidural hematoma in 1 case, cerebrospinal fluid leakage in 1 case and post-operative wound infection in 1 caseConclusions: In our study,microsurgical interruption of timely diagnosed SDAVF showed good and stable results over time.Bang. J Neurosurgery 2023; 12(2): 137-141